Combined oral contraceptive use increases HPV persistence but not new HPV detection in a cohort of women from Thailand - Morgan Marks (2018)
Background.Women diagnosed with cervical cancer report longer duration and more recent use of combined oral contraceptives (COCs). It is unclear how COC use impacts risk of cervical carcinogenesis.Methods.We estimated the risk of new human papillomavirus (HPV) DNA detection and persistence among 1135 human immunodeficiency virus (HIV)-negative women aged 20-37 years from Thailand who were followed for 18 months at 6-month intervals. Type-specific HPV DNA, demographic information, hormonal contraceptive use, sexual behavior, genital tract coinfection, and Papanicolaou test results were assessed at baseline and each follow-up.Results.Women who reported current COC use during follow-up were less likely to clear HPV infection compared with nonusers, independent of sexual behavior, and Papanicolaou test diagnosis (AHR: 0.67 [95% CI:. 49-.93]). Similar associations were not observed among women reporting current use of depomedroxyprogesterone acetate (DMPA). Neither COC nor DMPA use was significantly associated with new HPV DNA detection.Conclusions.These data do not support the hypothesis that contraceptive use is associated with cervical cancer risk via increased risk of HPV acquisition. The increased risk of HPV persistence observed among current COC users suggests a possible influence of female sex hormones on host response to HPV infection. © The Author 2011.